2020
DOI: 10.1140/epjst/e2020-000011-y
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rise and evaporation of a liquid in a corner between a plane and a cylinder: A model of imbibition into a nanofiber mat coating

Abstract: Wetting of surfaces with porous coating is relevant for a wide variety of technical applications, such as printing technologies and heat transfer enhancement. Imbibition and evaporation of liquids on surfaces covered with porous layers are responsible for significant improvement of cooling efficiency during drop impact cooling and flow boiling on such surfaces. Up to now, no reliable model exists which is able to predict the kinetics of imbibition coupled with evaporation on surfaces with porous coatings. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The power fitting of the plotted data showed that . Chatterjee et al 45 previously demonstrated that the drained volume evolves with time as , following the premise from Washburn’s law when evaporation is not significant during the imbibition and the substrate does not have intrinsic hydrophobic properties 43 , 49 , 50 . Therefore our result corroborates that in the initial moments, the droplet volume loss is dominated by spreading and imbibition.…”
Section: Resultsmentioning
confidence: 97%
“…The power fitting of the plotted data showed that . Chatterjee et al 45 previously demonstrated that the drained volume evolves with time as , following the premise from Washburn’s law when evaporation is not significant during the imbibition and the substrate does not have intrinsic hydrophobic properties 43 , 49 , 50 . Therefore our result corroborates that in the initial moments, the droplet volume loss is dominated by spreading and imbibition.…”
Section: Resultsmentioning
confidence: 97%
“…Pore-scale models have increasingly become a reliable tool for making predictions of two-phase flows through porous media; see e.g. [87,88]. Direct numerical simulation techniques based on solving the full Navier-Stokes equations provide an accurate solution for pore-scale analysis of multiphase flows in porous media.…”
Section: Moving Contact Lines On Arbitrary Geometriesmentioning
confidence: 99%